Analisis Pendekatan Culturally Responsive Teaching dalam Perangkat Pembelajaran IPAS Kelas IV SD Negeri 44 Kota Bengkulu (Kurikulum Merdeka) - Saputri, Rice; Dalifa; Yuliantini, Nani (JURIDIKDAS, 2025)
This research aims to describe the implementation of a culturally responsive teaching approach in the planning of science and social studies (IPAS) lessons for the fourth grade at SD Negeri 44 Bengkulu City. This study is qualitative, using a Content Analysis method. The subject of the research is the fourth grade A teacher at SDN 44 Bengkulu City, while the object of the research is the planning of IPAS lessons in 2022. The research instrument used is the human instrument (the researcher) with observation, interviews, and documentation guidelines. Data analysis focuses on lesson plans, and data collection techniques include observation, interviews, and documentation. Data validity techniques are ensured through triangulation. The results of the analysis of the culturally responsive teaching approach in the fourth-grade A IPAS lesson plans at SDN 44 Bengkulu City (Merdeka Curriculum) indicate that the teacher has developed teaching modules using this approach. This is evident in the core components of the teaching module, such as learning objectives, assessment, meaningful understanding, triggering questions, and learning activities that include culturally responsive teaching, along with the five components of culturally responsive teaching steps in the learning activities. The conclusion of this study is that the fourth grade A IPAS lesson plans at SD Negeri 44 Bengkulu City, developed by the teacher, have utilized the culturally responsive teaching approach.